A 10-point preoperative checklist: selecting patients for outpatient joint replacement surgery - Chowdhry, M; McPherson, EJ (BioMed Central, 2024)
Background: With advancements in perioperative care, joint replacement (JR) surgery is undergoing a transition from opacified in-patient institutions to nimble out-patient Ambulatory Surgical Centers (ASC). The goal of JR in ASC setting is safe patient discharge with subsequent rehabilitation without readmission. Multi-modal preoperative rehabilitation (MMPR) is a novel field of perioperative care, encompassing comprehensive parameters to ensure smooth transition from fitness for surgery to JR in outpatient setting. At present, there are no open-access schemes for selecting patients qualified for JR in the ASC setting. In this article, we propose an evidence-based, 10-point systematic evaluation of patients with target endpoints for MMPR to qualify patients for JR as an outpatient procedure. This checklist is a non-proprietary scheme serving as an initial framework for surgeons exploring surgery in the ASC setting. Body: We introduce factors for a prehabilitation scheme, called Checklist Outpatient-Joint Replacement (CO-JR) to qualify patients for outpatient JR surgery. These factors have been developed based on an extensive literature review and the significant experience of authors to incorporate variables that drive a successful outpatient JR procedure. The factors include patient education, psychiatric & cognitive ability, medical fitness, musculoskeletal capability, financial ability, transportation access, patient motivation, information technology (IT) capabilities, along with ability to recover independently at home postoperatively. The CO-JR scheme is under the process of validation at multiple institutions. We introduce this as a starting point for collaborative development of an open-access scheme for all surgeons to learn and adapt as needed for their respective global region. Conclusion: We established a non-proprietary 10-point CO-JR scheme, serving as a framework for surgeons to successfully select patients for JR surgery in the ASC setting. We encourage concomitant validation of this scheme globally. Our goal is to reach an international consensus on an open-access scheme, available for all surgeons to enrol patients for JR in the ASC setting, but modifiable to accommodate regional needs.